Prevalensi dan Determinan Stunting di Daerah Istimewa Yogyakarta: Analisis Data SSGI 2024 - Morrin Thohira; Arlina Azka; Nabila Vebiana Soviadi; Dewi Saptowati (Universitas Faletehan, 2025)
The decline in stunting prevalence nationally shows a positive trend, but challenges remain at the regional level, including in the Special Region of Yogyakarta (DIY). This study aims to analyze trends in stunting prevalence and its determinants in DIY Province, using data from the 2024 Indonesian Nutritional Status Survey (SSGI), to inform regional policy interventions. The method used is a descriptive, quantitative approach with a comparative analysis of national data. The data collection technique was carried out by accessing the 2024 SSGI Results Book in Figures at the link www.badankebijakan.kemkes.go.id. The results indicate that all districts/cities in DIY reported stunting prevalence rates below the national average in 2024, although disparities between regions are still evident, particularly in Gunungkidul Regency. Several prominent determinants include the high incidence of closely spaced pregnancies, low participation in prenatal classes, and the proportion of babies born with low birth weight and short birth length (LBW and SBL). Furthermore, access to growth monitoring, the quality of complementary feeding (MPASI), and adequate sanitation and drinking water also contribute significantly. These findings underscore the importance of sustainable, specific, and sensitive nutrition interventions, as well as a multisectoral approach involving families and communities. This study is expected to serve as a reference for local governments in developing evidence-based policies to accelerate stunting reduction in DIY.